The current state of development of social psychology at Taras Shevchenko National University of Kyiv - Kovalenko, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article presents analysis of the current state development of domestic social psychology. Based on the comparison of social psychology development condition in Russia and Ukraine are allocated the main areas, differences in subject of researches and outlines the prospects for their development. Analysis suggests that the actual for social psychology, in both countries, are problems associated with personality traits and its membership in various groups. The differences consists in the fact that Russia's social psychologists have gravitate to the expansion and amalgamation of subjects (macrosocial-psychology), and focuses on the phenomenon of patriotism. Ukrainian scientists accentuate attention on the problems that are associated with recent events in the East of Ukraine and their consequences. The prospects of Ukrainian researches are problems of theoretical psychology development, mass behavior and unorganized groups, as well an verification the classical experiments. Also are presented the main directions of socio-psychological researches at the department of social psychology.
Keywords: social psychology; object; research directions; prospects of research